Nominata de Pareceristas / Reviewers Nomination: 2010-2012 - Huff Júnior, Arnaldo Érico (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2011)
Nominata de Pareceristas / Reviewers Nomination: 2010-2012